2016
DOI: 10.1111/cea.12720
|View full text |Cite
|
Sign up to set email alerts
|

Does providing written dietary advice improve the ingestion of non‐allergic nuts in children with existing nut allergies? – A randomized controlled trial

Abstract: This dietary intervention did not improve non-allergic nut ingestion by nut allergic children. Hospital challenge increased introduction rates, whilst parentally reported child concern about a reaction reduced success. Non-allergic nut ingestion did not change quality of life or sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…We hypothesize that the families’ vision of cross‐contamination risk is an important factor leading to avoidance of all species that may be considered nuts or seeds in a culinary sense . Avoidance of species, of which specific allergens the child is not sensitized to, may be feasible considering the risk of cross‐contamination . However, the unnecessary avoidance may prevent the development of oral tolerance to these species …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the families’ vision of cross‐contamination risk is an important factor leading to avoidance of all species that may be considered nuts or seeds in a culinary sense . Avoidance of species, of which specific allergens the child is not sensitized to, may be feasible considering the risk of cross‐contamination . However, the unnecessary avoidance may prevent the development of oral tolerance to these species …”
Section: Discussionmentioning
confidence: 99%
“…32,33 Avoidance of species, of which specific allergens the child is not sensitized to, may be feasible considering the risk of cross-contamination. 33 However, the unnecessary avoidance may prevent the development of oral tolerance to these species. 34 One strength of our study is that all patients were double-blind placebo-control challenged.…”
Section: Discussionmentioning
confidence: 99%
“…22 It is still unknown whether ingestion of tolerated tree nuts ameliorates development of tolerance to other tree nuts, 23 or whether it prevents development of allergy to the tolerated nut, but it does increase the quality of life of individuals and for vegetarians allows another protein source to be included in the diet. 22 It is still unknown whether ingestion of tolerated tree nuts ameliorates development of tolerance to other tree nuts, 23 or whether it prevents development of allergy to the tolerated nut, but it does increase the quality of life of individuals and for vegetarians allows another protein source to be included in the diet.…”
Section: Peanut An D Tree Nut Allergymentioning
confidence: 99%
“…This may have implications for the way we discuss risk with patients affected by food allergy. Norman et al . showed that advice to eat nuts to which a child is not allergic was not followed at home, perhaps due to anxiety about the possibility of a severe reaction occurring in the home environment—however, a supervised food challenge was followed by home introduction in most cases.…”
Section: Clinical Allergymentioning
confidence: 99%
“…The MIRABEL study authors then went on to use cluster analysis to group PNA patients by clinical phenotype; further publications from this interesting observational study are keenly awaited. 117 In one of the most comprehensive reviews of fatal anaphylaxis in recent years, Mullins et al 118 120 showed that advice to eat nuts to which a child is not allergic was not followed at home, perhaps due to anxiety about the possibility of a severe reaction occurring in the home environment-however, a supervised food challenge was followed by home introduction in most cases. relation to BSACI guidelines.…”
Section: Food Allergy and Anaphylaxismentioning
confidence: 99%